Abstraction 1910-1940. (London : Annely Juda Fine Art, 1980)
Arp, Hans (Jean) ; Balla, Giacomo ; Bergmann-Michel, Ella ; Berlewi, Henryk ; Biederman, Charles ; Bill, Max ; Bolotowsky, Ilya ; Bomberg, David ; Bortnyik, Sándor ; Buchheister, Carl ; Buchholz, Erich ; Cahn, Marcelle ; Chashnik, Ilya ; Davis, Stuart ; Delaunay, Robert ; Delaunay, Sonia ; Dexel, Walter ; van Doesburg, Theo ; Domela, César ; Ermilov, Vassily ; Exter, Alexandra ; Fleischmann, Adolf Richard ; Gabo, Naum ; Goncharova, Natalia ; Gorin, Jean ; Hepworth, Barbara ; Herbin, Auguste ; Höch, Hannah ; Kandinsky, Wassily ; Kassak, Lajos ; Kliun, Ivan ; Klucis, Gustav ; Kupka, Frantisek ; Le Corbusier ; van der Leck, Bart ; Leger, Fernand ; Lissitzky, El ; Maatsch, Tilo ; Malevich, Kasimir ; Michel, Robert ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Moore, Henry ; Morton, Alistair ; Moss, Marlow ; Nicholson, Ben ; Péri, László ; Pevsner, Antoine ; Picabia, Francis ; Popova, Liubov ; Puni, Ivan ; Reichel, Hans ; Rodchenko, Alexander ; Russell, Morgan ; Schwitters, Kurt ; Stenberg, Vladimir ; Stephenson, Cecil ; Strzeminski, Wladyslaw ; Taeuber-Arp, Sophie ; Tatlin, Vladimir ; Udaltsova, Nadezhda ; Vantongerloo, Georges ; Vezelay, Paule ; Villon, Jacques ; Vordemberge-Gildewart, Friedrich
biog. per kunstenaar
Engels
Abstraction 1910-1940, Annely Juda Fine Art, London, 1 July - 27 September, 1980
boek